Virulence evolution in response to vaccination: the case of malaria. - Mackinnon, M; Gandon, S; Read, A (2008)
One theory of why some pathogens are virulent (i.e., they damage their host) is that they need to extract resources from their host in order to compete for transmission to new hosts, and this resource extraction can damage the host. Here we describe our studies in malaria that test and support this idea. We go on to show that host immunity can exacerbate selection for virulence and therefore that vaccines that reduce pathogen replication may select for more virulent pathogens, eroding the benefits of vaccination and putting the unvaccinated at greater risk. We suggest that in disease contexts where wild-type parasites can be transmitted through vaccinated hosts, evolutionary outcomes need to be considered.